2000
DOI: 10.1097/00001648-200007000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in Drinking Water in Relation to Morbidity and Mortality from Acute Myocardial Infarction

Abstract: We investigated the importance of magnesium and calcium in drinking water in relation to morbidity and mortality from acute myocardial infarction. Cases were men and women 50-74 years of age living in 18 Swedish municipalities who had suffered an acute myocardial infarction some time between October 1, 1994, and June 30, 1996. Controls were randomly selected from the same study base. We interviewed the surviving cases (N = 823) and controls (N = 853), focusing on risk factors for acute myocardial infarction. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 34 publications
4
62
0
3
Order By: Relevance
“…Contrastingly, five of the seven studies showed a statistically significant protective effect of drinking water magnesium against mortality from AMI ( Rubenowitz et al 1996Rubenowitz et al , 1999Rubenowitz et al , 2000, hypertensive disease ) and stroke (Yang 1998) for males and females.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Contrastingly, five of the seven studies showed a statistically significant protective effect of drinking water magnesium against mortality from AMI ( Rubenowitz et al 1996Rubenowitz et al , 1999Rubenowitz et al , 2000, hypertensive disease ) and stroke (Yang 1998) for males and females.…”
Section: Resultsmentioning
confidence: 80%
“…The remaining seven case control studies assessed concentrations of specific drinking water constituents, namely magnesium and calcium, and cardiovascular disease mortality. Of these, five studies reported no evidence of a statistically significant association between calcium concentrations and cardiovascular mortality with no consistent direction of association (Rubenowitz et al 1996(Rubenowitz et al , 2000Yang 1998;Rosenlund et al 2005). Two studies reported a protective effect of drinking water calcium on mortality from AMI for females (Rubenowitz et al 1999) and males and females combined (Yang et al 2006).…”
Section: Resultsmentioning
confidence: 98%
“…This concept has gained credibility over the past five decades from a large number of studies from different parts of our planet (4 -6, 27-29, 46, 48, 63, 67, 72); the death rates by sudden cardiac death are lower in hard-water areas than in soft-water areas. Despite the fact that the hardness of water is due to the concentration of Ca 2ϩ and/or Mg 2ϩ , the overwhelming evidence, to date, supports the idea that it is the Mg content that is responsible for most of the protective effects of hard water (28,29,38,46,48,63). More than 20 years ago, it was suggested that as little as 15-30 mg·l Ϫ1 ·day Ϫ1 of Mg 2ϩ in drinking water should be cardioprotective (46,48).…”
Section: H325mentioning
confidence: 99%
“…Over the past five decades, an accumulation of epidemiological and experimental data have indicated that a reduction in the dietary intake of Mg, as well as low Mg content in drinking water, is a risk factor for the development of hypertension, atherosclerosis, vasospasm, sudden cardiac death, stroke, and inflammatory conditions by ill-defined mechanisms (e.g., see Refs. 1,[4][5][6][17][18][19][27][28][29]35,38,46,48,49,63,64,65,67,72). Hypermagnesemic diets have been shown to ameliorate hypertension and atherogenesis (4,5,7,8,18,23,67).…”
mentioning
confidence: 99%
“…Most such diets in the U.S.A. show that 60 -80% of Americans are consuming only 185-235 mg Mg/day [4][5][6]. Low Mg content in drinking water found in areas of soft water and Mg-poor soil, is associated with high incidences of ischemic heart disease, severe atherosclerosis, coronary vasospasm, hypertension, hyperlipidemia, diabetes, and sudden cardiac death [4,[7][8][9][10][11][12][13][14]. Both animal and human studies have shown an inverse relationship between dietary intake of Mg and atherosclerosis [4,13,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%